The Association of Couples’ Feeling of Happiness with Differentiation of Self (DoS) and Early Object Relations with the Mediating Role of Religious Marital Satisfaction - jafari Soltanabadi , Arezu; Monirpour , Nader; mirzahoseini , hasan (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study aimed to determine the mediating role of religious marital satisfaction in the relationship between couples’ feeling of happiness with their differentiation of self (DoS) and early object relations. Methods: The present study was descriptive and correlational with a structural equation modeling approach. The statistical population of the study consisted of couples, who had been living together for 10 years in Tehran in 2020, and we selected 300 individuals by a convenience sampling method and included them in the study. To collect data, we utilized the Differentiation of Self Inventory (DSI) by Skowron (1998), the object relation quality inventory by Bell (1995), the feeling of happiness inventory by Lentz (2010), and the religious marital satisfaction inventory by Rezapour Mirsaleh (2014). We used structural equation modeling to analyze the data. Results: The results indicated that all indices of model fit with data had acceptable values ​​(P=0.01). According to the results, the differentiation of self and the quality of object relations had indirect effects on the feeling of happiness mediated by religious marital satisfaction at a low confidence interval of 0.11 and an upper limit of 0.26 at a significance level (P=0.01). Conclusion: According to the research results, counselors and psychologists active in the field of marriage can benefit from the present results to improve and enrich the process of education and promote mental health in families.